Effects of methamphetamine on neural responses to visual stimuli. - Van Hedger, Kathryne; Keedy, Sarah K.; Schertz, Kathryn E.; Berman, Marc G.; de Wit, Harriet (Psychopharmacology, 2019)
Rationale: The behavioral and reward-related effects of stimulant drugs have been studied extensively; yet the effect of stimulants on sensory processing is still relatively unknown. Prior brain imaging studies have shown that single doses of stimulant drugs increase neural function during cognitive and attentional processes. However, it is not clear if stimulant drugs such as methamphetamine (MA) affect neural responses to novel sensory stimuli, and whether these effects depend on the visual features of the stimuli. Objective: In this study, we examined the effects of a single dose of MA (20 mg oral) on neural activation in response to visual stimuli that varied on "non-straight edges" (NSE), a low-level visual feature that quantifies curved/fragmented edges and is related to perceived image complexity. Methods: Healthy adult participants (n = 18) completed two sessions in which they received MA and placebo in counterbalanced order before an fMRI scan where they viewed both high and low NSE images. Participants also completed measures of subjective drug effects throughout both sessions. Results: During both sessions, high NSE images activated primary visual cortex to a greater extent than low NSE images. Further, MA increased activation only for low NSE images in three areas of visual association cortex: left fusiform, right cingulate/precuneus, and posterior right middle temporal gyrus. This interaction was unrelated to subjective drug effects. Conclusions: These findings suggest that stimulant drugs may change the relative sensitivity of higher order sensory processing to increase visual attention when viewing less complex stimuli. Moreover, MA-induced alterations in this type of sensory processing appear to be independent of the drugs' ability to increase feelings of well-being.